Slow light in coupled-resonator-induced transparency - Totsuka, Kouki; Kobayashi, Norihiko; Tomita, Makoto (Physical review letters, 2007)
We performed optical pulse propagation experiments in a system in which two ultrahigh-Q silica microspheres of different diameters were coupled in tandem to a fiber taper to yield coupled-resonator-induced transparency. Nearly Gaussian-shaped optical pulses propagated with a large positive delay of 8.5 ns through a transparent frequency window, without significant attenuation, amplification, or pulse deformation, demonstrating classical analogy of the extremely slow light obtained with electromagnetically induced transparency.